2021
DOI: 10.3389/fcell.2021.671170
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions of Let-7e-5p in Promoting the Differentiation of MC3T3-E1 Cells

Abstract: MicroRNAs let-7c and let-7f, two members of the let-7 family, were involved in regulating osteoblast differentiation and have an important role in bone formation. Let-7e-5p, which also belonged to the let-7 family, presented in the differentiation of adipose-derived stem cells and mouse embryonic stem cells. However, the role of let-7e-5p in osteoblast differentiation was unclear. Thus, this study aimed to elucidate the function of let-7e-5p in osteoblast differentiation and its mechanism. Firstly, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In consistent with the studies, we also observed increased expression of Let-7d-5p , Let-7f-5p , Let-7i-5p in Ckip-1 silencing-induced M2 macrophages. Moreover, relevant studies have also shown that several subtypes, including Let-7f-5p , Let-7i-5p could promote osteoblast mineralization, the osteogenic differentiation of stem cells, and bone formation [ 34 , [38] , [39] , [40] ]. Further, the enhanced osteogenic differentiation was partially attributed to the delivered Let-7 miRNAs in exosomes [ 41 ], suggesting the possibility of exosomal transfer of Let-7 miRNAs from Ckip-1-silenced macrophages to cementoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with the studies, we also observed increased expression of Let-7d-5p , Let-7f-5p , Let-7i-5p in Ckip-1 silencing-induced M2 macrophages. Moreover, relevant studies have also shown that several subtypes, including Let-7f-5p , Let-7i-5p could promote osteoblast mineralization, the osteogenic differentiation of stem cells, and bone formation [ 34 , [38] , [39] , [40] ]. Further, the enhanced osteogenic differentiation was partially attributed to the delivered Let-7 miRNAs in exosomes [ 41 ], suggesting the possibility of exosomal transfer of Let-7 miRNAs from Ckip-1-silenced macrophages to cementoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The role of osterix is to induce the differentiation of osteoprogenitors into pre-osteoblasts. The osterix pathway affects the expression of OCN, which indicates that pre-osteoblasts have already differentiated into osteoblasts [ 39 ]. The previous report also indicated the differentiation of osteoblasts through the upregulation of RUNX2 and the role of osterix as an inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Since the A allele could be a risk factor for IS, individuals with the AA genotype may have a higher risk of developing IS. Studies have linked the let-7f genes with tumor cell growth, migration, and differentiation (28,29). Therefore, previous studies focused on the role of the rs17276588 polymorphism in the development Clinical and demographic ischemic stroke (IS) risk factors in the female population according to the least absolute shrinkage and selection operator (LASSO) binary logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Since the A allele could be a risk factor for IS, individuals with the AA genotype may have a higher risk of developing IS. Studies have linked the let-7f genes with tumor cell growth, migration, and differentiation ( 28 , 29 ). Therefore, previous studies focused on the role of the rs17276588 polymorphism in the development of various cancers ( 30 ).…”
Section: Discussionmentioning
confidence: 99%